2017
DOI: 10.11152/mu-921
|View full text |Cite
|
Sign up to set email alerts
|

Doppler ultrasonography combined with transient elastography improves the non-invasive assessment of fibrosis in patients with chronic liver diseases

Abstract: Aims: Accurate clinical assessment of liver fibrosis is essential and the aim of our study was to compare and combine hemodynamic Doppler ultrasonography, liver stiffness by transient elastography, and non-invasive serum biomarkers with the degree of fibrosis confirmed by liver biopsy, and thereby to determine the value of combining non-invasive method in the prediction significant liver fibrosis. Material and methods: We included 102 patients with chronic liver disease of various etiology. Each patient was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…On the contrary, Alempijevic et al found that HARI has no significant correlation with significant liver fibrosis and cirrhosis. This discrepancy may be due to the small sample size and presence of various etiologies in that study, unlike homogeneity in the etiologies of other studies 28 .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…On the contrary, Alempijevic et al found that HARI has no significant correlation with significant liver fibrosis and cirrhosis. This discrepancy may be due to the small sample size and presence of various etiologies in that study, unlike homogeneity in the etiologies of other studies 28 .…”
Section: Discussionmentioning
confidence: 57%
“…Better prediction rates are obtained by combining Doppler variables with non-invasive markers and transient elastography of liver stiffness. Combining Doppler parameters, non-invasive markers (APRI, ASPRI, and FIB-4) and transient elastography yielded the best model for predicting significant fibrosis, with sensitivity and specificity of 88.9 percent and 100 percent, respectively, 28 . On the other hand, we observe less accuracy of HARI in the evaluation of early degrees of fibrosis.…”
Section: Medical Journal Of Viral Hepatitis (Mjvh)mentioning
confidence: 99%